LINGUISTIC ANALYSIS OF PERSUASION STRATEGIES IN POLITICAL SPEECHES (Scientific journal of the Fergana State University, 2025)
Communication through language, which is unique to humanity, is a complex and multi-layered phenomenon. Its in-depth study is relevant not only within linguistics but also at the intersection of cultural studies, political science, and psychology. In particular, the analysis of persuasion strategies used in political speeches requires significant methodological approaches to understand the purposeful selection of linguistic units. This article is aimed at exploring persuasion strategies in political discourse through linguistic means from a scientific perspective.